Tax Evasion in Sales Cuts Registered by Electronic Cash Register - Maria Durisova; Beata Holkova; Michal Lekyr (Communications - Scientific letters of the University of Zilina, 2015)
Tax evasion is a persistent problem of public finances. Sales cuts registered by electronic cash register (hereinafter referred to as „ECR“) is part of tax evasion. The State, through constant changes in legislation, creates barriers against them, which are effective only in the short term. The paper is based on the documentation of administrative offences arising from demands and communications with the financial administration. It analyses the changes in the law relating to the elimination of tax evasion by recording sales of ECR and evaluates them. It applies a model approach for the identification of subjects and links in the system. Risky relationships between subjects are exposed and menas of their elimination are proposed. It emphasises the important position of ICT in ECR, identifies difficult places in hardware and software, and suggests areas for improvement.